Pedagogical Challenges Facing The Teaching Business Studies in Secondary Schools in Bauchi State, Nigeria - Abdulrazak Mohammed; Hassan Abdullahi (MO.RI Publishing, 2022)
The study determines the Pedagogical challenges facing the teaching of business studies in Bauchi State, Nigeria. Two research questions guided the study and two null hypotheses were formulated and tested at 0.05 level of significance. The descriptive survey research design was used for the study. The population of the study comprised 248 business studies teachers from secondary schools in Bauchi State. Since the population size is manageable, the researchers used all populations. The researchers developed a structured questionnaire for data collection. The instrument was validated by two experts from the rank of senior lecturer and above in the department of Test and Measurement of Nasarawa State University, Keffi. Cronbach Alpha method was used to test the reliability of the instrument which yielded a coefficient value of 0.77. Mean and standard deviation was used to answer the research questions while a t-test was used to test the two null hypotheses formulated for the study at 0.05 level of significance. The finding indicated among others, that some Business studies courses are taught mostly by unqualified teachers. Data analysis revealed that some of the teachers were not familiar with the curriculum and since some of the teachers were not trained, they set internal examinations that only tested the low levels of the cognitive domain that is knowledge and comprehension while the national examinations tested all the levels of the cognitive domain. The study concludes that the Government should employ qualified lecturers in the area of Business Studies in the state, providing appropriate resources, retraining teachers in pedagogical competency needs. Appropriate recommendations were made including retraining of the teachers.